(untitled) (Bangladesh Rice Journal, 2023)
A study was aimed at modifying and manufacturing a power weeder at the local workshop using locally available material and evaluating its performance in the condition of Bangladesh. The Bangladesh Rice Research Institute’s Farm Machinery and Post-harvest Technology (FMPHT) division (BRRI) took the initiative to fabricate a power weeder using locally available materials. In the wetland of the BRRI research field and farmer’s field at Jogitola of Gazipur district, the developed power weeder was tested during the boro season of 2017-2018. The average weeding efficiency of the power weeder was 80.38% and 81.43% at the research and farmers’ field respectively. The percent of tiller damage was observed 2.78% and 2.81% respectively. 910 m2 h-1 (0.091 ha h-1) was the average effective field capacity of the power weeder. After 5 days, the percentage of weeds revived for power weeder was observed at 32.26% and 34.90% at the BRRI research and farmers’ fields, respectively. Weed biomass was found 35.43 gm m-2 in a farmer’s field and 30.88 gm m-2 in the BRRI research field, Gazipur. This machine can be run by one man/woman easily. The weight of the complete weeder is 18.3 kg. The benefit-cost ratio of the weeder is 1.85. Farmers can use this weeder in wetland conditions. In the line transplanted wetland field conditions, the power weeder was found suitable for controlling weeds with minimum standing water. Bangladesh Rice J.26 (1): 47-57, 2022